Small worlds - Bruno Codenotti; Luca Foschini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
In this tutorial we present some basic ideas behind the notion of Small World. We review the state-of-the-art in the field, and put emphasis on some recent developments, in connection with analyzing the structure of the Web.
Keywords: 330